Safety and immunogenicity of co-administered MF59-adjuvanted 2009 pandemic and plain 2009–10 seasonal influenza vaccines in rheumatoid arthritis patients on biologicals. (9th June 2014) - Milanetti, F; Germano, V; Nisini, R; Donatelli, I; Di Martino, A; Facchini, M; Ferlito, C; Cappella, A; Crialesi, D; Caporuscio, S; Biselli, R; Rossi, F; et al.
Summary: Rheumatoid arthritis (RA) patients under immunosuppressive therapy are particularly susceptible to infections, mainly of the respiratory tract, thus vaccination may represent a strategy to reduce their incidence in this vulnerable population. In the 2009–10 influenza season, the safety and immunogenicity of co-administered non-adjuvanted seasonal and MF59-adjuvanted pandemic influenza vaccines were evaluated in this study in 30 RA patients under therapy with anti-tumour necrosis factor (TNF)-α agents or Abatacept and in 13 healthy controls (HC). Patients and HC underwent clinical and laboratory evaluation before (T0), 1 (T1) and 6 months (T2) after vaccinations. No severe adverse reactions, but a significant increase in total mild side effects in patients versus  HC were observed. Both influenza vaccines fulfilled the three criteria of the Committee for Proprietary Medicinal Products (CPMP). Seroconversion rate for any viral strain in patients and HC was, respectively, 68 versus 45 for H1-A/Brisbane/59/07, 72 versus 81 for H3-A/Brisbane/10/07, 68 versus 54 for B/Brisbane/60/08 and 81 versus 54 for A/California/7/2009. A slight increase in activated interferon (IFN)-γ-, TNF-α- or interleukin (IL)-17A-secreting T cells at T1 compared to T0, followed by a reduction at T2 in both patients and HC, was registered. In conclusion, simultaneous administration of adjuvanted pandemic and non-adjuvanted seasonal influenza vaccines is safe and highly immunogenic. The largely overlapping results between patients and HC, in terms of antibody response and cytokine-producing T cells, may represent further evidence for vaccine safety and immunogenicity in RA patients on biologicals.